Characteristics and Outcomes of Patients with Acute Myocardial Infarction at Non-PCI Capable Hospitals in 2007 and in 2014. (4th October 2015) - Kalinauskiene, Egle; Gerviene, Dalia; Sabeckyte, Inga; Naudziunas, Albinas
Abstract : Background . There is little known about whether characteristics and outcomes of patients with acute myocardial infarction (AMI) have changed over the years in non-PCI capable hospitals in real-life. Our aim was to assess them between 2007 and 2014. Methods . It was a retrospective cohort study. Characteristics and in-hospital mortality (standardized in cases of different characteristics between the groups by original simple method) were assessed for all patients with non-ST elevation myocardial infarction (NSTEMI) and ST elevation myocardial infarction (STEMI) at two non-PCI capable hospitals: one in 2007 (n = 104 ) and another in 2014 (n = 58 ). Results . In 2014, females were older than in 2007 (80.18 ± 7.54 versus 76.15 ± 8.77, p = 0.011 ), males were younger (71.61 ± 11.22 versus 79.20 ± 7.63, p = 0.019 ), less had renal failure (RF) (19% versus 34.6%, p < 0.0001 ) and reinfarction (13.8% versus 35.6%, p < 0.0001 ), and the proportion of males (31% versus 43.3%, p = 0.001 ) and the proportion of NSTEMI (60.3 versus 69.2, p < 0.0001 ) decreased. In cases of STEMI there were no differences in patient characteristics. STEMI (18.8% versus 21.7%) and standardized mortalities by gender, RF, and reinfarction NSTEMI (19.47%, 15.34%, and 17.5%, resp., versus 17.1%) showed no differences between 2007 and 2014. Conclusions . There were some differences in patient characteristics but not in mortality for AMI at non-PCI capable hospitals between 2007 and 2014.